Women's COPD - Zysman, Maéva; Raherison-Semjen, Chantal (Frontiers in Medicine, 2022)
Chronic obstructive pulmonary disease (COPD) is no longer a respiratory disease that predominantly affects men, to the point where the prevalence among women has equaled that of men since 2008, partly due to their increasing exposure to tobacco and to biomass fuels. Indeed, COPD has become the leading cause of death in women in the USA. A higher susceptibility of female to smoking and pollutants could explain this phenomenon. Besides, the clinical presentation appears different among women with more frequent breathlessness, anxiety or depression, lung cancer (especially adenocarcinoma), undernutrition and osteoporosis. Quality of life is also more significantly impaired in women. The theories advanced to explain these differences involve the role of estrogens, smaller bronchi, impaired gas exchange in the lungs and smoking habits. Usual medications (bronchodilators, ICS) demonstrated similar trends for exacerbation prevention and lung function improvement in men and women. There is an urgent need to recognize the increasing burden of COPD in women and therefore to facilitate global improvements in disease management (smoking cessation, pulmonary rehabilitation…) in half of the population. Nevertheless, important limitations to the treatment of women with COPD include greater under-diagnosis than in men, fewer spirometry tests and medical consultations. In conclusion there is an urgent need to recognize the increasing burden of COPD in women and therefore to facilitate globally improvements in disease management in this specific population.